HUKUM SEORANG WANITA YANG MAKMUM KEPADA SEORANG LELAKI YANG BUKAN MUHRIM - Niki Alma Febriana Fauzi (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2014)
This study discusses the congregation law a woman to a man is not mahram. In society, consciously or unconsciously habit congregation woman to a man become commonplace. This raises questions regarding how the law? A tradition relates that the Prophet Muhammad, had been a priest of a beautiful woman who is not mahram. The hadith is weak status, but by looking at a few other reasons and arguments, concluded that the law of the congregation woman to a man who is not mahram is allowed.